SISTEM INFORMASI SIMPAN PINJAM PADA KPSP SETIA KAWAN NONGKOJAJAR BERBASIS WEB - Istikhomah; Linda Suvi Rahmawati (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2024)
Savings and loan transaction is an activity that is running on the unit Savings and Loan KPSP (Koperasi Peternakan Sapi Perah) Setia Kawan Nongkojajar. Savings and loan activities running in a computerized, but when the project is implemented, there are several obstacles in recording transactions derived from the data and the data Payday loan payments resulting calculation error occurs. There is also the difficulty in finding members installments history. The purpose of this research is to develop an information system that can handle every transaction so that this information system is expected to be one alternative for savings and loans unit in the process of saving and loan service members. The use of systems development methods, can provide a solution to the system running. Results of research conducted resulted that the proposed system can help the performance of the unit Savings and Loan KPSP (Koperasi Peternakan Sapi Perah) Setia Kawan Nongkojajar.